A multiobjective post-sales guarantee and repair services network design problem - Yıldız, Gazi Bilal; Soylu, Banu (International journal of production economics, 2019)
In this paper, we consider a biobjective post-sales guarantee and repair services network design problem. One of the objective functions minimizes the total transportation cost of the network, while the other one minimizes the total tardiness of returned products from the targeted delivery duration. Although the motivation of our problem emanates from the repair services network of a mobile phone company, proposed models and algorithms can easily be adapted to any type of products. The mobile phone customers are sensitive to delays and thus decreasing the tardiness improves the customer satisfaction. However, due to intense competition among mobile phone companies, the total cost of the repair services network should also be minimized. We analyze the tradeoff between these objective functions and discuss the properties of the Pareto frontier. We are able to find the Pareto frontier exactly for small size networks. For large size networks, we propose a variable neighborhood search (VNS) based heuristic to approximate the Pareto frontier. We perform an application and experiments on the current network of a mobile company and present alternatives to the decision maker. •A multiobjective reverse logistics network design problem is considered.•The Pareto frontiers of the main problem and subproblems are analyzed.•Small/medium size test problems can be solved exactly.•A VNS based heuristic is proposed for large size problems.•For a mobile phone company, alternative warehouse locations and solutions are presented.